2021
DOI: 10.1037/neu0000722
|View full text |Cite
|
Sign up to set email alerts
|

Performance validity and symptom validity tests: Are they measuring different constructs?

Abstract: Objective: To evaluate the relationships among performance validity, symptom validity, symptom self-report, and objective cognitive testing. Method: Combat Veterans (N = 338) completed a neurocognitive assessment battery and several self-report symptom measures assessing depression, posttraumatic stress disorder (PTSD) symptoms, sleep quality, pain interference, and neurobehavioral complaints. All participants also completed two performance validity tests (PVTs) and one stand-alone symptom validity test (SVT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…To our knowledge, no previous study has explored these relationships within a mixed neuropsychiatric sample with PVTs derived from (or appearing to be derived from) diverse cognitive modalities. By addressing gap in the literature, these findings can be generalized to populations beyond the VA and forensic/medicolegal contexts where most of this research has been conducted (e.g., Copeland et al, 2015;Gervais et al, 2007;Ord et al, 2021;Van Dyke et al, 2013;Whitney et al, 2008). Additionally, results were consistent with previous research showing that performance on SVTs and PVTs provide nonredundant validity information, even within diverse populations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To our knowledge, no previous study has explored these relationships within a mixed neuropsychiatric sample with PVTs derived from (or appearing to be derived from) diverse cognitive modalities. By addressing gap in the literature, these findings can be generalized to populations beyond the VA and forensic/medicolegal contexts where most of this research has been conducted (e.g., Copeland et al, 2015;Gervais et al, 2007;Ord et al, 2021;Van Dyke et al, 2013;Whitney et al, 2008). Additionally, results were consistent with previous research showing that performance on SVTs and PVTs provide nonredundant validity information, even within diverse populations.…”
Section: Discussionsupporting
confidence: 82%
“…To date, prior studies examining general relationships between SVT and PVT performance have yielded equivocal findings. Similarly, some recent studies have also demonstrated that symptom and performance validity represent distinct constructs in the context of adult ADHD evaluations (e.g., Leib et al, 2021;White et al, 2022) and neuropsychological evaluations in Veteran Affairs (VA) settings (e.g., Bomyea et al, 2020;Ingram et al, 2019Ingram et al, , 2020Ord et al, 2021). For instance, Aase et al (2021) and Shura et al (2021) found that PVTs and SVTs were largely dissociable among post-deployment veterans with conditions including posttraumatic stress disorder (PTSD) and concussion/mild traumatic brain injury (TBI).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, associations between performance-based validity measures and self-report scales are usually only moderate or, in some studies, even absent (e.g., Grossi et al, 2017;Ingram et al, 2020;Whiteside et al, 2020). Performance validity and symptom validity appear to constitute two related but distinct concepts (Ord et al, 2021;van Dyke et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…However, these results are consistent with subsequent studies by the same research group (Erdodi, 2021; Erdodi, Kirsch, et al, 2018). The divergence of the evidence on the psychogenic interference hypothesis (Tarachow, 1947) applied to PVT research has a number of potential explanations: methodological, instrumentation, or sampling artifacts, a diagnosis- or context-specific relationship or an imperfect and poorly understood association between performance and symptom validity (Abeare, Razvi, et al, 2021; Carvalho et al, 2021; Cutler, Sirianni, et al, 2022; Gaasedelen et al, 2019; Gegner et al, 2022; Ord, Shura, et al, 2021; Sabelli et al, 2021).…”
Section: Discussionmentioning
confidence: 99%